Mitigation of Voltage Sag for Motor Loads in Distribution Systems Using DSTATCOM - Kumar, Abhishek (My University, 2011)
Distribution system, as the name suggest, is the medium through which power is distributed among the end consumers. Distribution systems are comparatively not as stiff as grid systems, so large starting currents and objectionable voltage drop during the starting of an induction motor could be critical for the entire system. Thus DSTATCOM is an effective solution for power systems facing such power quality problems. This report deals with one of the potential applications of distribution static compensator (DSTATCOM) to industrial systems for mitigation of voltage dip problem. The dip in voltage is generally encountered during the starting of an induction motor. The model of DSTATCOM connected in shunt configuration to a three phase source feeding dynamic motor loads is developed using Simulink of MATLAB software. Simulated results demonstrate that DSTATCOM can be considered as a viable solution for solving such voltage dip problems. This thesis work aims at developing a DSTATCOM for induction machines with reduced voltage dip.
M.E. (EIED)
Keywords: Voltage Sag for Motor Loads; DSTATCOM